INTERNATIONAL EXPERIENCE OF ORGANIZING SCHOOL NUTRITION - V.R. Kuchma; Zh.Yu. Gorelova (Вопросы современной педиатрии)
The experience of organizing school nutrition in Europe and usais analyzed. It is noted that long term programs aimed at optimizing schoolchildren nutrition have a beneficial effect on the children's health, culture of their nutrition and quality of life. The importance of carrying out similar programs in Russia is beyond any doubt: according to population research, the basic principles of good nutrition are often not observed, and school breakfasts and lunches do not correspond to the age physiological needs of children and teenagers for nutrient materials and energy. In this situation, the available experience of using vitaminbenriched products as well as vitamin and mineral complexes in children will permit to quickly resolve the existing problems of the improper, and sometimes, insufficient, nutrition.Key words: school nutrition, organization, international experience.